Re-designing the Road to Success Programme (RSP) as a Tutorial: Blended Mode - Maogi, Kedibone Ivory (University of the Witwatersrand, Johannesburg, 2024)
Courses are still commonly characterised as blended without any relation to appropriate and pedagogically sound methodologies and practices. Merely adding an online component to the existing (face-to-face) classroom content should not be considered a ‘good’ blend. My argument in this thesis is that blended learning should be underpinned by sound theory, pedagogy and practice that extends the design and review beyond the mode (percentage online /offline and synchronous /asynchronous) discussion. To ascertain how a Road to Success Programme (RSP) could be reviewed and redesigned as a blended learning offering, a rubric was created using definitions gleaned from the literature on blended learning, Constructivism as learning theory, blended learning models, design principles, approaches, practices and Community of Inquiry framework. In this qualitative study, I created and piloted a rubric as data collection tool to review the RSP course. I employed a phased approach to data analysis, starting with simple statistics (numbers), followed by qualitative summaries and a Community of Inquiry/CoI (social constructivist) theoretical and analytical lens. The main findings suggest that the pedagogical principles, particularly the teaching, social, and cognitive presence provide a useful framework both for the design and review of blended courses, to extend it beyond an online/offline exercise. The study recommends a deeper engagement with course design elements (beyond the organisation and teaching of content and the use of technology) to instead consider how these elements intersect with each other and how the review and redesign of blended learning offerings could be strengthened.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Blended Learning; Community of Inquiry; Constructivism; Course review and Road to Success Programme; SDG-4: Quality education